Altered Metabolism of Phospholipases, Diacylglycerols, Endocannabinoids, and N-Acylethanolamines in Patients with Mastocytosis. (1st July 2019) - Ferrara, Anne Lise; Piscitelli, Fabiana; Petraroli, Angelica; Parente, Roberta; Galdiero, Maria Rosaria; Varricchi, Gilda; Marone, Giancarlo; Triggiani, Massimo; Di Marzo, Vincenzo; Loffredo, Stefania
Abstract : Background . Mastocytosis is a condition characterized by the expansion and accumulation of mast cells (MCs) in various organs. The symptoms are related to the increased release of MC-derived mediators that exert local and distant effects. MCs are a source and target of phospholipase enzymes (PLs), which catalyze the cleavage of membrane phospholipids releasing lipid mediators (e.g., diacylglycerols (DAGs) and the endocannabinoid (EC) 2-arachidonoylglycerol (2-AG)). To date, there are no data on the role of these lipid mediators in mastocytosis. Here, we analyzed plasma levels of PLA2, PLC, DAG, ECs, and EC-related N -acylethanolamines in patients with mastocytosis. Methods . In 23 patients with mastocytosis and 23 healthy individuals, we measured plasma PLA2 and PLC activities, DAG, 2-AG, anandamide (AEA), palmitoylethanolamide (PEA), and oleoylethanolamide (OEA). Results . Plasma PLA2 and PLC activities were increased in mastocytosis patients compared to controls. Concentrations of DAG (18:1 20:4 and 18:0 20:4), two second messengers produced by PLC, were higher in mastocytosis compared to controls, whereas the concentrations of their metabolite, 2-AG, were not altered. AEA was decreased in mastocytosis patients compared to controls; by contrast, AEA congener, PEA, was increased. PLA2 and PLC activities were increased only in patients with mediator-related symptoms. Moreover, PLC activity was positively correlated with disease severity and tryptase concentrations. By contrast, AEA was negatively correlated with tryptase concentrations. Conclusions . PLs and some lipid mediators are altered in patients with mastocytosis. Our results may pave the way for investigating the functions of these mediators in the pathophysiology of mastocytosis and provide new potential biomarkers and therapeutic targets.